2023
DOI: 10.2147/idr.s404747
|View full text |Cite
|
Sign up to set email alerts
|

6084 Cases of Adult Tetanus from China: A Literature Analysis

Abstract: Objective To describe the clinical characteristics, treatments, and outcomes of tetanus and determine the most appropriate focus for tetanus prevention and treatment to reduce morbidity and mortality in China. Methods Four databases, including the Chinese Bio-Medical Literature Database, Chinese National Knowledge Infrastructure, Chinese Scientific Journal Database, and Wan-fang Data, were searched from 1 January, 2000 to 30 October, 2022. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Although China eliminated maternal and neonatal tetanus by 2012 without using the vaccine as other countries typically have, this success is primarily due to improved birth hygiene and increased in-hospital delivery rates. These results may lead some to believe TT vaccination boosters are unnecessary, but adult tetanus cases have been frequently reported in Chinese literature ( Gou et al, 2023 ). Tetanus antibody levels tend to decrease with age, putting adults over 20 years old at high risk of tetanus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although China eliminated maternal and neonatal tetanus by 2012 without using the vaccine as other countries typically have, this success is primarily due to improved birth hygiene and increased in-hospital delivery rates. These results may lead some to believe TT vaccination boosters are unnecessary, but adult tetanus cases have been frequently reported in Chinese literature ( Gou et al, 2023 ). Tetanus antibody levels tend to decrease with age, putting adults over 20 years old at high risk of tetanus infection.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of epidemiological data on non-neonatal tetanus in China, but in some reports, certain hospitals admitted more than 30 tetanus patients in a year ( Gou et al, 2023 ). Furthermore, seroprevalence data found that low antibody levels are common in young adults and antibody levels tend to decrease with age ( Nazik et al, 2020 ; Zhang et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic disturbances mimicking "sympathetic storming" can frequently occur, so pancuronium should be avoided because of its potential to inhibit catecholamine reuptake. 21,64 Imperative to treatment are debridement of the wound and use of antibiotic therapy against C. tetani.…”
Section: Neuromuscular Complicationsmentioning
confidence: 99%
“…This results in spasmodic motor muscle paralysis ( 1 ). Disease onset typically occurs within 3–20 days (average: 7 days) after infection, with a reported incubation period of up to 120 days ( 2 ). Following symptoms, including neck tension, tongue-twisting, and injured limb prodding, the patient progressively loses the ability to walk, causing general paralysis.…”
Section: Introductionmentioning
confidence: 99%
“…Following symptoms, including neck tension, tongue-twisting, and injured limb prodding, the patient progressively loses the ability to walk, causing general paralysis. In severe cases, respiratory muscle paralysis can lead to death ( 2 4 ).…”
Section: Introductionmentioning
confidence: 99%